Integral indicators of the swimming techniques effectiveness of highly qualified crawl-stroke swimmers - Krylov, A.; Gorelov, A.; Tretyakov, A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
It is known that prominent world-class swimmers are characterized by the manifestation of specific abilities. These abilities allow to constantly maintain a stable speed swimming of different segments of the distance. In this case, highly qualified swimmers can increase the maximum speed of swimming on a segment of a given length. They achieve this by increasing the total external mechanical power. In this case, swimmers keep, and in some cases even reduce the power of the stroke. It is implemented the phase-specific principle of creating driving forces during each phase. At the same time, the principle of creating driving forces is common to all swimming locomotion. The article gives a rationale for the effectiveness of the integral criterion application for evaluating swimming techniques. The integral criterion for evaluating the swimming technique was applied at remote speeds of the entire spectrum of the competitive front crawl swimming program. Material . The study involved 9 highly qualified crawl-stroke swimmers, members of Russia national team. The age of the participants ranged from 18 to 24 years. It is studied the kinematic and kinetic characteristics of the front crawl swimming technique of highly qualified athletes at various competitive distances. The studies applied video recording of swimmer`s movements with OLYMPUS TG-5 camera (Vietnam) from a depth of 4.5 m. Three luminous markers located on the swimmer`s hips were applied to record the dynamic parameters of swimmer`s movements. The results of the swims were processed with Natatometry™ (Russia). Results . It was determined that swimmers demonstrated high indices of the intra-cyclic dynamic index (ICDI - Intra Cycle Dynamic Index) and the dynamic coordination index of the swimming cycle (DCI - Dynamic Coordination Index) at speeds in medium distances relative to speeds at sprint distances. Swimmers demonstrate the ability to generate a significant amount of promotional efforts at 100 m distance that ensure the achievement of high speeds. It is established that no general trends in ICDI changes in individual structural phases of the stroke. This indicates the demonstration of individual specific features in the swimming technique of each athlete. Conclusion . It is considered the feasibility of applying the integral indicators ICDI and DCI for a quantitative assessment of the intra cycle promotion forces interaction and hydrodynamic resistance forces arising at the level of an integral biomechanical system of the swimming cycle.